2022
DOI: 10.3389/fnins.2022.941244
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Spontaneous Neural Activity and Its Interaction With Pain and Emotion in Temporomandibular Disorders

Abstract: Background and PurposeTemporomandibular disorders (TMD), especially pain-related TMD, are closely related to social and psychological factors. We aimed to measure changes in spontaneous brain activity and its related functional connectivity (FC), as well as FC characteristics within the mood-regulating circuits (MRC) in TMD patients by resting-state functional magnetic resonance imaging (RS-fMRI), and to analyze the relationship between these parameters and emotional symptoms.Materials and MethodsTwenty-one ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“… Chen et al, 2018 ). Pain-related alterations in rsFC between the parahippocampal gyrus and amygdala to cortical regions have also been previously identified, with the direction of association reported dependent on the cortical region and population (X. F. Chen et al, 2022 , Desmarteaux et al, 2021 , Mao et al, 2022 , Verriotis et al, 2022 ). In addition to their roles in pain processing, the parahippocampal gyrus and amygdala are involved in processes of emotion, memory, attention, and conditional learning through association of stimuli with positive or negative outcomes ( Aminoff et al, 2013 , Gallagher and Chiba, 1996 ).…”
Section: Discussionmentioning
confidence: 71%
“… Chen et al, 2018 ). Pain-related alterations in rsFC between the parahippocampal gyrus and amygdala to cortical regions have also been previously identified, with the direction of association reported dependent on the cortical region and population (X. F. Chen et al, 2022 , Desmarteaux et al, 2021 , Mao et al, 2022 , Verriotis et al, 2022 ). In addition to their roles in pain processing, the parahippocampal gyrus and amygdala are involved in processes of emotion, memory, attention, and conditional learning through association of stimuli with positive or negative outcomes ( Aminoff et al, 2013 , Gallagher and Chiba, 1996 ).…”
Section: Discussionmentioning
confidence: 71%
“…TMD pain in these studies was recognized as a source of peripheral neuropathy causing inflammation in the central nervous system After removing the source of peripheral inflammation, we can see immediate significant changes in brain activity and signal overload during examination by functional magnetic resonance imaging ( Barkhordarian et al, 2020 ). Chen et al (2022) also indicated neurobiological evidence that the occurrence and development of negative emotions in TMD patients may be related to the dysfunction of dopamine pathway components induced by chronic pain. The abnormal dopaminergic functional connection linking orofacial pain and depression may indicate right treatment of TMD comorbidity with negative emotion by the application of serotonin reuptake inhibitor drugs ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 91%
“… Chen et al (2022) also indicated neurobiological evidence that the occurrence and development of negative emotions in TMD patients may be related to the dysfunction of dopamine pathway components induced by chronic pain. The abnormal dopaminergic functional connection linking orofacial pain and depression may indicate right treatment of TMD comorbidity with negative emotion by the application of serotonin reuptake inhibitor drugs ( Chen et al, 2022 ). Also studies conducted by Suenaga et al have shown that TMD pain is most often associated with the thalamus, the primary somatosensory cortex, the insula, and the anterior and mid-cingulate cortices ( Suenaga et al, 2016 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The activation of PHG is related with emotional memory encoding ( 69 ). Chen et al ( 70 ) found a positive correlation between the activation of right PHG and depressive symptoms. The cuneus belongs to the visual areas; the activation of the sensory-related brain areas is a prerequisite to the generation of consciousness ( 8 , 71 ).…”
Section: Discussionmentioning
confidence: 99%